STUDI DESKRIPTIF KELOMPOK RISIKO WANITA USIA SUBUR DI WILAYAH KERJA UPT PUSKESMAS GUNTUNG - Hartuti, Hartuti; Dewi Iswandari, Novita; Fajriannor TM, M. (LPPM Universitas Sari Mulia, 2024)
Background: Women of Reproductive Age (WRA) are defined by the Ministry of Health of the Republic of Indonesia as women between the ages of 15 and 49. Women in this age group fall into the